Menanamkan Nilai Adab sebelum Ilmu dalam Pembelajaran Upaya Pembentukan Karakter dan Etika Peserta Didik - Talitha Dahayu Ardiningrum (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
In recent years, education has placed greater emphasis on academic achievement, often overlooking the importance of character and ethical development in students. However, instilling the value of adab (proper manners) before knowledge is essential as a foundational aspect of the learning process. Adab encompasses attitudes such as respect for teachers, honesty, responsibility, and politeness, which contribute to forming ethical individuals. This study aims to explore the significance of adab values in education as an effort to cultivate students' character and ethics from an early age. The research uses a literature review method by analyzing various sources from Islamic education and character education theories. The findings reveal that the integration of adab values can be achieved through teacher role modeling, fostering positive habits within the school environment, and embedding these values into learning materials. When consistently applied, these approaches create a conducive learning atmosphere and develop students who are not only intellectually capable but also morally upright. The study implies that a balanced approach to education, which emphasizes both knowledge and adab, should be instilled early in both school and family settings